Mot 90⁰ syd, en rapport - Kristensen, Monica (Polarboken, 1988)
Keywords: Antarktis; ekspedisjoner; glasiologi

Iceberg calving and deterioration in Antarctica - Kristensen, Monica (Progress in Physical Geography: Earth and Environment, 1983)
Keywords: Antarktis; glasiologi; innlandsis; isbreer; isbrem; kalving

Modelling of antarctic tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
The prediction of the motions of a tabular iceberg in a seaway is a problem which cannot be solved with a simple approach. The main difficulty lies in the size and mass of the iceberg, which produce frequency-dependent hydrodynamical effects as it moves in the water. Specifically, any solution must take into account both the added inertia and the generation of surface waves caused by the motions of the berg. Early attempts at modelling, which did not include these terms, could not accurately predict the complicated response behaviour seen in field data. In this paper we discuss some modifications to a two-dimensional simulation of floating bodies in waves, which must be applied when the motions and the hydro-dynamical pressures beneath tabular icebergs are required.
Keywords: Antarktis; Sørishavet; bølger; glasiologi; isbreer

Automatic collection of tilt and strain data from tabular icebergs - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
Keywords: Antarktis; forskning; glasiologi; isbreer

Tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A; Moore, Stuart C (Nature, 1982)
Keywords: Antarktis; bølger; ekspedisjoner; glasiologi; havet; isbreer